Work anxiety and performance: Systematic literature review - Rofiqi Rofiqi; Sopiah Sopiah (Universitas Nusa Cendana, 2026)
This systematic review aims to examine the influence of innovation strategies on firm competitive advantage and to establish a theoretical foundation for future research on innovation and organizational competitiveness, with a specific focus on work anxiety and employee performance. The review follows the PRISMA framework and analyzes nine studies published between 2019 and 2024. Relevant literature was sourced from major academic databases, including Taylor & Francis, ScienceDirect, Springer, Wiley, Oxford Academic, SAGE Journals, and BMC. The findings indicate that most of the reviewed studies emphasize a strong relationship between work-related anxiety and employee performance, suggesting that psychological strain remains an important factor influencing organizational outcomes. However, despite the growing number of publications in recent years, the review identifies a significant gap in empirical studies exploring work anxiety from multiple perspectives and contexts. This indicates that the field is still developing and requires further in-depth investigation to better understand how work anxiety affects performance across different organizational settings. Overall, the study highlights the need for more comprehensive and multidisciplinary research to advance theoretical and practical understanding of work anxiety and its implications for employee performance. Keywords: Work Anxiety; Employee Performance; Innovation Strategy; Systematic Review; PRISMA